A study of students' dispositions to tertiary education in selected modern arabic schools in Ibadan (2015)
The percentage of students seeking admission into tertiary institutions to study either Arabic or Islamic Studies is worrisome and thus calls for an investigation. To this end, the study investigated the attitudes of the students of modem Arabic schools in Ibadan to tertiary education with a bid to establishing the factors wholly responsible for or partially resulting in the rarity recorded in the admission to study the twin subjects of Arabic and Islamic Studies at tertiary level. The study employed purposive sampling technique in selecting four modem Arabic Schools in the city of Ibadan where one hundred and seventy-two (172) copies of a questionnaire were administered among the students. Also, eleven (11) students of these modem Arabic schools were randomly sampled for interviews. Responses elicited from the respondents were quantitatively and qualitatively analysed to answer three research questions. From the findings, it was observed that virtually all the sampled Arabic schools in Ibadanland do prepare their students adequately for the rigours of tertiary education in addition to self-equipment of most of the students who are already secondary school certificate holders. Unfortunately, this statistical revelation does not reflect in the quota of students being admitted to study Arabic, Islamic Studies and other related courses at the tertiary stage in the Southwest. The findings revealed that some graduates of these Arabic schools who find themselves in various tertiary institutions in Nigeria and abroad are influenced by the outstanding status and achievements of their role models. This is without prejudice to the obstacle put by poverty in the way of many others to pursue tertiary education